Characterization of invasive meningococcal disease case isolates in Atlantic Canada, 2014 to 2020: spatial–temporal variations of clones and predicted meningococcal B vaccine coverage. Issue 12 (16th December 2022) - Tsang, Raymond S. W.; Law, Dennis K.S.; Zhou, Jianwei; Haldane, David; Garceau, Richard; Zahariadis, George; Mead, Kristen; Alexander, David
Abstract : Introduction. Invasive meningococcal disease (IMD) caused by Neisseria meningitidis may show temporal and geographical changes in both the epidemiology and the characteristics of the strains involved. Gap statement. A study that examined invasive N. meningitidis causing IMD in Atlantic Canada from 2009 to 2013 was published in 2014. Data from subsequent years have not been described. Aim. This study examined the molecular epidemiology of IMD in four Atlantic Provinces of Canada as well as potential serogroup B (MenB) vaccine coverage. Methods. Individual IMD case isolates recovered from 2014 to 2020 were analysed for serotype and serosubtype antigens as well as by whole-genome sequencing (WGS) for prediction of potential MenB vaccine coverage. Results. Of the 56 IMD isolates, 42, 8, 5 and 1 were MenB, serogroup Y, serogroup W (MenW) and serogroup C, respectively. Geographical differences in the distribution of MenB clones revealed concentration of sequence type (ST)-269 clonal complex (cc) and ST-60 cc in Newfoundland and Labrador, while ST-41/44 cc (particularly ST-154) was predominantly found in New Brunswick and Nova Scotia. Core genome multi-locus sequence typing (cgMLST) also separated the New Brunswick and Nova Scotia ST-154 isolates into two clusters, with differences in their nhba and penA alleles. Furthermore, cgMLST also separated the ST-269 cc isolates in Atlantic Canada into the ST-1611 and the ST-269/ST-8924 clusters, with the latter showing high similarity to the ST-269 that first emerged in the Province of Quebec. Genetic Meningococcal Antigen Typing System showed that 54.8 % of MenB were predicted to be covered by the MenB vaccine Bexsero, with a further 38.1 % potentially covered by virtue of the presence of genes that encoded factor H-binding protein variant 1 proteins. Meningococcal deduced vaccine antigen reactivity predicted from WGS data showed that 95.3 % of MenB were covered by Trumenba. Four cases of IMD due to MenW ST-11 cc were also identified, with the first case found in 2018. Conclusions. This study provided evidence concerning the dynamics of N. meningitidis strains causing IMD in Atlantic Canada, with both geographical and temporal differences found. MenB vaccine appeared to provide good coverage of MenB IMD, especially towards the predominant strain of ST-154.